Viable urban redevelopments – exchanging equity for energy efficiency - Kuronen, Matti; Luoma-Halkola, Jukka; Junnila, Seppo; Heywood, Chris; Majamaa, Wisa (International Journal of Strategic Property Management, 2011)
This research paper examines the potential of urban refurbishment projects to accommodate ambitious low-energy solutions. This can be made possible by aligning the interests of the community (energy conservation) and owner (increased value) through redeveloping the land owned by present residents being used as equity to finance the low-energy upgrades to existing dwellings. This holistic view of urban redevelopment is presented as a financial analysis model. In the paper a real-life case of the Siltamäki suburb in Helsinki, Finland, is presented and analysed. The approach used to interpret the case is the Public-Private-People Partnership (4P). It was found that the developed model allows several different scenarios to be presented for decision-making without compromising any of the stakeholder’s financial interests and, that owner-occupiers can, as a result, have new energy efficient refurbishment options. The originality of this paper lies in the way the owner-occupiers’ viewpoint is included in a refurbishment and redevelopment process. First Publish Online: 5 Oct 2011